Junior High Mathematics Teacher Resource Manual 1988. Curriculum Support - Alberta Dept. of Education, Edmonton; Alberta Dept. of Education, Edmonton ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1988)
This resource manual was designed to enable teachers to help students: (1) solve problems and to grow in their capability to deal with new or different situations; (2) use mathematics as a tool in the pursuit of personal goals and aspirations; and (3) develop a positive self-concept and a positive attitude toward mathematics and lifelong learning. The content of this manual is divided into six strands: problem solving, number systems and operations, ratio and proportion, measurement and geometry, data management, and algebra. The skills and concepts within these strands are sequenced over three grades taking into account the developmental nature of mathematics and of the learner. Five contexts are used in this program: (1) critical and creative thinking; (2) language of mathematics; (3) computational facility and estimation; (4) technological process; and (5) relevancy and application. In each objective, clarification or example, effective suggestions and integration of problem solving and technology are described. Evaluation strategy, time allocation in each grade, usage of manipulatives, and grade 9 curriculum specifications are appended. (YP)
ERIC Note: For a related document, see ED 294 763. Colored pages may not reproduce well.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Foreign Countries; Instructional Materials; Junior High Schools; Mathematical Concepts; Mathematical Enrichment; Mathematics Curriculum; Mathematics Education; Mathematics Instruction; Mathematics Materials; Mathematics Teachers; Middle Schools; Resource Materials; Secondary Education; Secondary School Mathematics; Canada; Guides, Classroom -- Teacher